AB0865 Do asas, asdas and basdai therapy response evaluation translate the same information?. (12th June 2018) - Eusébio, M.; Gomes, J.L.; Bernardes, M.; Pinto, P.; Santos, H.; Tavares-Costa, J.; Dias, J.; Pimenta, S.; Domingues, L.; Crespo, C.; Maia, S.; Martins, F.; et al.
Abstract : Background: The ASAS-EULAR recommendations for the continuation of biological Disease-Modifying Anti-rheumatic Drugs (DMARD) suggest the evaluation of patients after at least 12 weeks of treatment by either the Ankylosing Spondylitis (AS) Disease Activity Score – C reactive protein (ASDAS-CRP) or by the Bath AS Disease Activity Index (BASDAI). For ASDAS-CRP, a Minimal Clinical Important Difference (MCID) ≥1.1 is necessary, while for the total BASDAI score a 50% reduction or a change of ≥2.0 points is considered clinically relevant. In clinical trials, the Assessment in Ankylosing Spondyloarthritis (ASAS) response criteria – ASAS 20, ASAS 40 and ASAS 70 – are still the most frequent primary outcome measures to evaluate improvement in treatment response. However, in clinical practice the BASDAI is still routinely used. Objectives: The aim of this work was to assess the concordance/agreement between different therapeutic outcome measures, such as the ASAS response criteria, ΔASDAS-CRP and BASDAI 50. Methods: Data from 54 patients who fulfilled the modified New York criteria for AS were collected at baseline, weeks 2 and 14 post-treatment with Adalimumab. Pearson's correlation (PCCs) and the Cohen's Kappa coefficients were calculated for the three scores. Results: A strong correlation was found between the three scores throughout the visits: rho=−0.676 for ASDAS/ASAS, rho=−0.807 for ASAS/BASDAI, and rho=0.786 for BASDAI/ASDAS (all PCCs with p<0.001). Additionally, when the categorization in different disease activity states and response levels was performed, PCCs revealed significant concordance/agreement between the three scores' cut-offs (see table 1). The individuals categorised as responders, by eitheir BASDAI50 or ΔASDAS ≥1.1, have shown similar clinical characteristics (Erythrocyte Sedimentation Rate, CRP, AS Quality of Life Scale and Bath AS Functional Index). Importantly, when more stringent measures of ASAS response criteria and ASDAS were used (i.e. ASAS 70 and ASDAS≥2.1) the agreement with BASDAI values decreased. Conclusions: Our results suggest that the ASAS response criteria, ΔASDAS-CRP and BASDAI 50 report the same clinical information. Hence, the clinician's decision should still be consistent independently of the score adopted. However, this study also highlights the importance of establishing a new and more stringent BASDAI cut-off, in alignment with ASDAS-CRP'≥2.1 and ASAS 70. Disclosure of Interest: None declared